2008
DOI: 10.1590/s0104-66322008000200010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and optimization of non enzymatic browning of “cajuina” during thermal treatment

Abstract: "Cajuina" is a very popular drink in the Brazilian northeastern region and is produced by clarifying cashew apple juice. To preserve "cajuina" from chancing, the clarified cashew apple juice is submitted to thermal treatment where a desired final color should be obtained. To optimize color formation while maintaining high vitamin C and low 5-hydroxymethylfurfural (5-HMF) concentrations the thermal treatment of "cajuina" needs to be studied and the non enzymatic mechanism should be better understood and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 13 publications
1
24
0
6
Order By: Relevance
“…These results show that apple contains sucrose besides invert sugar as glucose and fructose. Invert sugars are one of the main factors of the non-enzymatic browning, affecting the quality of fruit juices (Damasceno et al 2008). Damasceno et al (2008) ruled out a reduction less than 4 % in invert sugar content as a possibble cause for formation of nonenzymatic browning in cashew apple juice.…”
Section: Discussionmentioning
confidence: 99%
“…These results show that apple contains sucrose besides invert sugar as glucose and fructose. Invert sugars are one of the main factors of the non-enzymatic browning, affecting the quality of fruit juices (Damasceno et al 2008). Damasceno et al (2008) ruled out a reduction less than 4 % in invert sugar content as a possibble cause for formation of nonenzymatic browning in cashew apple juice.…”
Section: Discussionmentioning
confidence: 99%
“…Le chauffage du jus pendant un temps relativement long engendre des jus beaucoup plus sombres. La même observation a été faite par Damasceno et al (2008) au cours du traitement thermique du cajuina à 80 et 121 °C. Pour ces auteurs, la perte en acide ascorbique au cours du traitement thermique pourrait être le principal facteur responsable du brunissement du jus.…”
Section: Discussionunclassified
“…Akinwalé (2000), Damasceno et al (2008) et Adou et al (2012) ont obtenu respectivement un pH de 4,15 ; 4,4 ; 4,37 à 4,5 pour des jus brut de pomme de cajou. Akinwalé en 2000 a obtenu une acidité titrable de 0,48% contre 0,55 à 0,59% pour le jus de pomme de cajou mûre selon les travaux de Adou et al (2012).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The HMF results were not detectable (<1.0 mg/L) throughout the study, indicating that the pasteurization conditions were not too severe to produce browning. On a study of cashew apple juice, Damasceno, Fernandes, Magalhaes, and Brito (2008) showed that at 100 • C more than 100 min were needed to detect formation of HMF.…”
Section: Safety and Thermal Impact Study -Part Imentioning
confidence: 99%